Biosynthèse de nanoparticules à partird'extraits de Solenostemma argel et Anastatica hierochuntica,et évaluation de leuractivitébiologique - Derki MAROUA (université d'eloud, 2025)
الملخص: في السنوات الأخيرة، حظيت الجسيمات النانوية المحضَّرة بطرق خضراء باهتمام متزايد من طرف الباحثين، لما تتميز به من خصائص محسَّنة وتطبيقات واسعة. في هذه الدراسة، تم اعتماد نهج أخضر ومستدام لتحضير جسيمات أكسيد الزنك النانوية (ZnO NPs) حيويًا باستعمال مزيج من مستخلصي نباتي Anastatica hierochuntica L. وSolenostemma argel. تمثل الهدف الرئيس في التغلب على مشكلات عدم التحكم في حجم الجسيمات أثناء التحضير الحيوي، وحدود طرق التحسين التقليدية أحادية العامل. ولتحقيق ذلك، استُخدم تصميم Box–Behnken (BBD) في إطار منهجية سطح الاستجابة (RSM) لدراسة تأثير ثلاثة عوامل رئيسية في التصنيع، وهي: تركيز خلات الزنك (ZA-C)، ودرجة حرارة التفاعل (REA-T)، ودرجة حرارة التلدين (AN-T) على حجم الجسيمات النانوية. أكدت تقنيات التوصيف المختلفة، بما في ذلك المطيافية فوق البنفسجية–المرئية (UV–Vis)، ومطيافية الأشعة تحت الحمراء بتحويل فورييه (FTIR)، والحيود بالأشعة السينية (XRD)، والمجهر الإلكتروني الماسح (SEM)، والتحليل الطيفي للأشعة السينية المشتّتة للطاقة (EDX)، التحضير الناجح لجسيمات ZnO NPs نقية ذات بنية بلورية سداسية وفجوة نطاق قدرها eV 3.26. أظهرت الجسيمات النانوية المحضَّرة شكلاً كرويًا إلى شبه ممدود، بأحجام تراوحت بين nm 32 و66. بيّن التحليل الإحصائي صلاحية النموذج التربيعي، حيث وصف البيانات التجريبية بدقة مع قيم عالية لكلٍّ من R² المتوقعة (%95.42) وR² المعدَّلة (%97.93). كما أظهرت نتائج تحليل التباين (ANOVA) تأثيرًا معنويًا لجميع العوامل المدروسة ومعظم تأثيراتها المشترك في حجم جسيمات ZnO NPs، باستثناء تآثيرالمشترك بين حرارة التفاعل والتلدين (REA-T × AN-T). وباستخدام التحسين العددي ودالة الرغبة، تم تحديد ظروف مثلى سمحت بالحصول على حجم أدنى للجسيمات بلغ nm 31. إضافةً إلى ذلك، تم تقييم النشاطين المضاد للأكسدة والمضاد للبكتيريا لعينات مختلفة من ZnO NPs، حيث أظهرت جميع العينات قدرة ملحوظة على تثبيط الجذور الحرة وكفاءة معتبرة ضد السلالات البكتيرية المختبرة. تبرز هذه الدراسة كفاءة منهجية سطح الاستجابة في التحكم بحجم جسيمات ZnONPs المحضَّرة حيويًا، وتفتح آفاقًا لإدراج معايير إضافية لتحسين أدق لحجم الجسيمات في الدراسات المستقبلية. Abstract: In recent years, green-synthesized nanoparticles have attracted increasing attention due to their enhanced properties and wide range of potential applications. In this study, a green and sustainable approach was employed to biosynthesize zinc oxide nanoparticles(ZnO NPs) using a mixture of Anastatica hierochuntica L and Solenostemma argel plant extracts. The primary aim was to address the common challenges of uncontrolled nanoparticle size in biosynthesis and the limitations of traditional one-factor-at-a-time optimization methods. To this end, the Box–Behnken design (BBD) of response surface methodology (RSM) was applied to systematically investigate the effects of three key synthesis parameters zinc acetate concentration (ZA-C), reaction temperature (REA-T), and annealing temperature (AN-T) on ZnONP size. The successful synthesis of pure ZnONPs with a hexagonal crystal system and a band gap of 3.26 eV was confirmed by ultraviolet–visible spectroscopy (UV–Vis), Fourier-transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), scanning electron microscopy (SEM), and energy-dispersive X-ray spectroscopy (EDX). SEM images revealed predominantly spherical to slightly elongated nanoparticles with sizes ranging from 32 to 66 nm. Statistical analysis validated the quadratic RSM model, which accurately predicted and fitted the experimental data, with a predicted R² of 95.42% and an adjusted R² of 97.93%. ANOVA results indicated that ZnO NPs size is significantly affected by all the investigated parameters as well as most of their interactions, except for the REA-T × AN-T interaction. Numerical optimization using the desirability function yielded optimal synthesis conditions that afforded a minimum particle size of 31 nm. In addition, the antioxidant and antibacterial activities of the different ZnONPs samples were evaluated. All tested samples exhibited marked free-radical scavenging activity and notable antibacterial efficacy. Overall, this study demonstrates the efficiency of RSM in controlling the size of biosynthesized ZnO NPs and highlights the potential of this green approach for further refinement of nanoparticle size control in future work.
أطروحة دكتوراء
Keywords: جسيمات أكسيد الزنك النانوية (ZnONPs); التصنيع الحيوي; التحسين; منهجية سطح الاستجابة (RSM); تصميم Box–Behnken; التحكم في الحجم; النشاط المضاد للأكسدة; النشاط المضاد للبكتيريا